(untitled) (Third Sector Social Economic Review, 2025)
The aim of the study is to descriptively examine and compare total current health expenditures and changes in their public and private components in Türkiye during the period 2010-2023. In line with the aim of the study, the scope of the research comprises Türkiye’s current health expenditures and their public and private components between 2010 and 2023. Research data was obtained from secondary sources published publicly by official institutions. In the study, which adopted a descriptive design, the data was organised and analysed using Microsoft Excel 2016 software. The findings showed a steady nominal increase in current health expenditures, while public sovereignty was maintained. Public current health expenditures constituted approximately 78-79% of total expenditures until 2019, with the private sector share rising to approximately 24% in 2023. Real growth findings indicate that the nominal increases in recent years were largely driven by price effects. Public dominance continues in Türkiye’s healthcare financing structure, and public financing has ensured the resilience of the system during economic shocks and the pandemic. However, it has been shown that the inadequacy of the share of Gross Domestic Product (GDP) allocated to health, rising inflation and private expenditure pose challenges for the long-term sustainability of health financing. The findings of the study highlight the importance of increasing the share of GDP allocated to health in Türkiye, revealing the need for sustainable and improved resource allocation in health financing.